2016
DOI: 10.3389/fpls.2016.00706
|View full text |Cite
|
Sign up to set email alerts
|

Different Growth Promoting Effects of Endophytic Bacteria on Invasive and Native Clonal Plants

Abstract: The role of the interactions between endophytes and alien plants has been unclear yet in plant invasion. We used a completely germ-free culture system to quantify the plant growth-promoting (PGP) effects of endophytic bacteria Bacillus sp. on aseptic seedlings of Wedelia trilobata and of its native clonal congener W. chinensis. The endophytic bacteria did not affect the growth of W. chinensis, but they significantly promoted the growth of W. trilobata. With the PGP effects of endophytic bacteria, relative chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…Chen et al (2013) found that invasive Alternanthera philoxeroides was more tolerant to fluctuating water depth than their native, congeneric Alternanthera sessilis in wetland and showed better photosynthetic capacity. Similar results were noted by (Xiao et al, 2010) W. trilobata is native to tropical region of south America (Wang et al, 2012;Weber, Sun, & Li, 2008) and is a clonal evergreen creeping herb which was also found in southern region of China in 1970s on a large scale Dai, Fu, Wan, et al, 2016b;Qi et al, 2014). In China, initially it was introduced as a groundcover species but later it spread rapidly from garden to roadsides and then to the agricultural fields (Song, Chow, Sun, Li, & Peng, 2010;Talukdar & Talukdar, 2013).…”
supporting
confidence: 67%
“…Chen et al (2013) found that invasive Alternanthera philoxeroides was more tolerant to fluctuating water depth than their native, congeneric Alternanthera sessilis in wetland and showed better photosynthetic capacity. Similar results were noted by (Xiao et al, 2010) W. trilobata is native to tropical region of south America (Wang et al, 2012;Weber, Sun, & Li, 2008) and is a clonal evergreen creeping herb which was also found in southern region of China in 1970s on a large scale Dai, Fu, Wan, et al, 2016b;Qi et al, 2014). In China, initially it was introduced as a groundcover species but later it spread rapidly from garden to roadsides and then to the agricultural fields (Song, Chow, Sun, Li, & Peng, 2010;Talukdar & Talukdar, 2013).…”
supporting
confidence: 67%
“…Moreover, each plant part was immersed and shaken in 1.2% sodium hypochlorite solution (NaClO) for 30 min, and then washed with sterile water three times (2 min per wash). The last sterile water rinse (100 μL) was plated onto Luria-Bertani (LB) agar medium and incubated for 24 h (at 30°C) in order to test the efficacy of disinfection for each plant part surface ( Dai et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sorghum halepense , an invasive plant that thrives on low-nitrogen grasslands, contains endogenous nitrogen-fixing bacteria that improve the availability of soil resources (Rout & Chrzanowski, 2009; Rout et al, 2013). The effects of rhizo- and endophytic bacteria on the invasion of exotic plants are species-specific and vary across environmental conditions (Long, Schmidt & Baldwin, 2008; Rout & Callaway, 2012; Dai et al, 2016). While previous studies have been conducted to investigate fungal diversity in invasive plants (Shipunov et al, 2008; Mei et al, 2014), it is equally important that the bacterial diversity associated with invasive plants is explored to understand the plant–bacteria interactions that occur in the invasion mechanisms of alien plants.…”
Section: Introductionmentioning
confidence: 99%